2022
DOI: 10.3390/ijerph192316160
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Obesity and Childhood Dental Caries in the United States

Abstract: Background: Childhood obesity and dental caries are prevalent chronic, multifactorial conditions with adverse health consequences and considerable healthcare costs. The aims of this study were: (1) to evaluate the relationship between obesity and dental caries among young children using multiple definitions for both conditions, and (2) to evaluate the role of family socioeconomic status (SES) and the child’s intake of added sugars in explaining this association. Methods: Data from 2775 2–5-year-olds children f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…However, after controlling for common risk factors, this association became non-statistically significant when obesity was measured using BMI and changed in direction when BAZ was used as an obesity measure. Similar findings have been reported in a recent US study which concluded that the caries-obesity relationship is influenced by how they are measured and attenuated by common risk factors [ 14 ]. In addition, a negative association between dental caries and BAZ has been observed in studies conducted in Bangladesh [ 28 ] and Saudi Arabia [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, after controlling for common risk factors, this association became non-statistically significant when obesity was measured using BMI and changed in direction when BAZ was used as an obesity measure. Similar findings have been reported in a recent US study which concluded that the caries-obesity relationship is influenced by how they are measured and attenuated by common risk factors [ 14 ]. In addition, a negative association between dental caries and BAZ has been observed in studies conducted in Bangladesh [ 28 ] and Saudi Arabia [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the current study supports the notion that obesity and caries risk are not directly related; instead, common risk factors drive the development of both conditions. Furthermore, these factors are influenced by wider social determinants [ 14 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other medical and health professionals could easily apply the scale to identify gradual changes in a person’s diet between specific time points in order to enlighten them on common risk factors for dental caries development. The scale could be used as a tool to improve the understanding of the relationship of the diet to oral-health and other conditions, such as obesity and overweight status [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Streptococcus mutans and Lactobacillus spp., the two primary caries-associated pathogens belonging to the phylum Firmicutes, are more abundant in the gut microbiota of children with obesity, suggesting that oral Firmicutes may reflect the gut condition of preschool-aged children with obesity ( Reis et al., 2022 ). However, other studies have suggested that the relationship between dental caries in primary teeth and obesity can vary based on the definitions of obesity and dental caries ( Piovesan et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%